2020
DOI: 10.3390/ijms22010332
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Gram-Positive Bacteria Exposure Elicits Distinct Cytokine Responses In Vitro

Abstract: During pregnancy, infections caused by the gram-positive bacteria Enterococcus faecalis (E. faecalis), Streptococcus agalacticae (S. agalacticae), and Staphylococcus aureus (S. aureus) are major reasons for preterm labor, neonatal prematurity, meningitis, or sepsis. Here, we propose cytokine responses to bacterial infections by the immature perinatal immune system as central players in the pathogenesis of preterm birth and neonatal sepsis. We aimed to close the gap in knowledge about such cytokine responses by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Elevated cord plasma cytokines, including CXCL8, have been previously observed in some neonates born to SARS-CoV-2-positive mothers 17 . Similarly, increased cord plasma CXCL8 has been observed after in utero exposure to infection 36,37 , suggesting that maternal infection can directly influence fetal CXCL8. Raised neonatal inflammatory markers do appear to be related to the maternal infection status at the time of birth, as such profiles are less obvious in neonates born to mothers with recovered infection.…”
Section: Discussionmentioning
confidence: 93%
“…Elevated cord plasma cytokines, including CXCL8, have been previously observed in some neonates born to SARS-CoV-2-positive mothers 17 . Similarly, increased cord plasma CXCL8 has been observed after in utero exposure to infection 36,37 , suggesting that maternal infection can directly influence fetal CXCL8. Raised neonatal inflammatory markers do appear to be related to the maternal infection status at the time of birth, as such profiles are less obvious in neonates born to mothers with recovered infection.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, bacteria such as Escherichia, Shigella (both belonging to Proteobacteria), and Enterobacter (also belonging to Proteobacteria) exhibited negative associations with fecal concentrations of acetic, propionic, butyric, and valeric acids. It has been reported that Escherichia and Enterobacter, enriched in the gut of PE patients, can lead to excessive inflammatory responses ( Reuschel et al., 2020 ). These findings suggest that changes in fecal SCFA levels align with variations in GM abundance in the PE group ( Chang et al., 2020 ).…”
Section: Relationship Between Scfas and Gm Alterationsmentioning
confidence: 99%
“…Furthermore, Al-Judaibi et al (2021) reported that three common species were found in 15 of 19 stool samples of the preterm infants in the NICU, which were affected by commonly used antibiotics, with significant resistance of Enterococcus and K. pneumoniae to some of the tested antibiotics. Enterococcus is also a common pathogen in the NICU, and Enterococcus infection is the major cause of neonatal prematurity, meningitis, and sepsis ( Reuschel et al, 2020 ). In another study, Enterococcus and Streptococcus were enriched in the non-probiotic formula-feeding group of premature infants ( Chi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that probiotics, including Bifidobacterium supplementation in preterm infants, may prevent serious morbidities ( Plummer et al, 2021 ). Another study showed that routine administration of a multispecies probiotic containing Bifidobacterium and Lactobacillus to very low birth weight infants had no significant impact on the NEC incidence ( Juber et al, 2021 ) which shown the different results compared with reference Reuschel et al (2020) .…”
Section: Discussionmentioning
confidence: 99%